Survival and prognostic factors in pediatric patients with medulloblastoma treated at a national pediatric hospital in Peru: a retrospective cohort - Flores-Sanchez, JD (2023)
OBJECTIVE The objectives of this study were to determine the overall survival (OS) and event-free survival (EFS) rates of patients with medulloblastoma treated in a national pediatric hospital in Peru, as well as to identify demographic, clinical, imaging, postoperative, and histopathological characteristics and prognostic factors associated with OS and EFS. METHODS The authors conducted a retrospective study analyzing information from the medical records of children with a diagnosis of medulloblastoma who underwent surgical treatment at the Instituto Nacional de Salud del Niño—San Borja, a public hospital in Lima, Peru, from 2015 to 2020. Clinical-epidemiological variables, degree of disease extension, risk stratification, extent of resection, postoperative complications, status of oncological treatment received, histological subtype, and neurological sequelae were taken into account. The Kaplan-Meier method and Cox regression analysis were used to estimate OS, EFS, and prognostic factors. RESULTS Of the 57 children evaluated with complete medical records, only 22 children (38.6%) underwent complete oncological treatment. OS was 37% (95% CI 0.25–0.55) at 48 months. EFS was 44% (95% CI 0.31–0.61) at 23 months. High-risk stratification—meaning patients with ≥ 1.5 cm2 of residual postoperative tumor, those younger than 3 years, those with disseminated disease (HR 9.69, 95% CI 1.40–67.0, p = 0.02), and those who underwent subtotal resection (HR 3.78, 95% CI 1.09–13.2, p = 0.04)—was negatively associated with OS. Failure to receive complete oncological treatment was negatively associated with OS (HR 20.0, 95% CI 4.84–82.6, p < 0.001) and EFS (HR 7.82, 95% CI 2.47–24.7, p < 0.001). CONCLUSIONS OS and EFS of patients with medulloblastoma in the author’s milieu are below those reported in developed countries. Incomplete treatment and treatment abandonment in the authors’ cohort were also high compared with high-income country statistics. Failure to complete oncological treatment was the most important factor associated with poor prognosis, both in terms of OS and EFS. High-risk patients and subtotal resection were negatively associated with OS. Interventions are needed to promote the completion of adjuvant oncological therapy for medulloblastoma in the disadvantaged Peruvian population.